1983
DOI: 10.1039/f19837901335
|View full text |Cite
|
Sign up to set email alerts
|

Photo-oxidation of metalloporphyrins in aqueous solution

Abstract: Water-soluble, diamagnetic metalloporphyrins have been prepared which contain either zinc@), palladium(@ or tin(1v) ions as the central metals and their photophysical properties have been measured in dilute aqueous solution. All the compounds undergo efficient intersystem crossing to form long-lived excited triplet states that can participate in electron-transfer reactions. Thus excitation of the metalloporphyrin in dilute aqueous solution containing an appropriate electron acceptor, such as iron(m), may resul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
49
0

Year Published

1998
1998
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 86 publications
(51 citation statements)
references
References 0 publications
2
49
0
Order By: Relevance
“…56 The photophysical and electrochemical data were used to construct energy level diagrams including combinations of WOC, PS and sacrificial electron acceptor (Na 2 S 2 O 8 ) in phosphate buffer at pH 7.0 ( Figure 4). Highly exothermic triplet-state one-electron transfer (ΔG = −1.01 eV) from photogenerated 3 Pt(II)-TCPP (E 1/2 (Pt III/II ) = -0.40 V) to S 2 O 8 2in buffer solution 16 …”
Section: Electrochemical Characterizationmentioning
confidence: 99%
“…56 The photophysical and electrochemical data were used to construct energy level diagrams including combinations of WOC, PS and sacrificial electron acceptor (Na 2 S 2 O 8 ) in phosphate buffer at pH 7.0 ( Figure 4). Highly exothermic triplet-state one-electron transfer (ΔG = −1.01 eV) from photogenerated 3 Pt(II)-TCPP (E 1/2 (Pt III/II ) = -0.40 V) to S 2 O 8 2in buffer solution 16 …”
Section: Electrochemical Characterizationmentioning
confidence: 99%
“…200 mV over that of the corresponding neutral species13 and provides good solubility in water 14. Earlier studies focused on the use of ZnTMePyP 4+ as a photosensitizer for light‐driven water oxidation in the presence of heterogeneous RuO 2 /TiO 2 or homogeneous Co 2+ catalysts 15. These attempts failed, and oxygen was not detected as a product.…”
Section: Introductionmentioning
confidence: 99%
“…The existence of this type of compound was first suggested by Woodward [1] in 1961, whose prediction was confirmed about a decade later when Dolphin et al [2] reported the first synthesis of a metalloisoporphyrin ( 4 ) from zinc 5,10,15,20-tetraphenylporphyrin by way of electrochemical oxidation. Other methods for directly generating metallo-isoporphyrins since then include peroxide oxidation [3, 4] and photooxidation [58]. …”
Section: Introductionmentioning
confidence: 99%